Novel aqueous zinc ion battery electrolyte additive with steric hindrance effect and application thereof
By using electrolyte additives with steric hindrance effects and soluble zinc salts in aqueous zinc ion batteries, the problem of zinc dendrites is solved, and the cycling performance and capacity retention rate of the battery is significantly improved.
Patent Information
- Application Number
- CN202411856379.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
Zinc dendrites growth is the main problem that restricts the actual application of aqueous zinc ion batteries. The existing technology has failed to effectively solve the contradiction between fast electrochemical kinetics and slow mass transfer, resulting in uneven growth of zinc negative electrodes and even short-circuiting the battery.
An electrolyte additive with steric hindering effect, such as 4-aminomethylcyclohexanecarboxylic acid, 4-(aminomethyl)cyclohexanoformate hydrochloride, 4-(aminomethyl)cyclohexanylamine, etc., is prepared in combination with soluble zinc salts, such as zinc sulfate, a new aqueous zinc ion battery electrolyte is prepared to balance zinc ion transport and reduction kinetics.
By introducing electrolyte additives, the growth of zinc dendrites is inhibited, the activity of free water in the electrolyte is reduced, and the flat and uniform zinc deposition is promoted, which significantly improves the circulation performance and capacity retention rate of water-based zinc ion batteries and extends the battery service life.
Smart Images

Figure HDA0005191914510000011 
Figure HDA0005191914510000012 
Figure HDA0005191914510000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to a novel aqueous zinc ion battery steric hindrance electrolyte and application thereof. Background Art
[0002] Compared with aqueous battery systems, current lithium-ion batteries using organic electrolytes face great challenges, including limited lithium resources, high prices, safety hazards, and environmental issues. -1 , volumetric capacity is 5855mAh·cm -3 Rechargeable aqueous zinc-ion batteries (ZIBs) have attracted extensive attention as a promising alternative to lithium-ion batteries due to the attractive advantages of low-energy consumption, lower reduction potential (−0.76 V vs SHE), and aqueous electrolytes (high ionic conductivity and high safety).
[0003] However, zinc dendrite growth is the main problem that restricts the practical application of aqueous zinc ion batteries. The reason is that the contradiction between fast electrochemical kinetics and slow mass transfer may produce a significant zinc ion concentration gradient on the electrode surface, resulting in uneven growth of metal Zn and even battery short circuit, which is often overlooked in previous studies. Electrolyte optimization is a simple, convenient and effective way to regulate zinc-electrolyte interface chemistry. Therefore, developing a suitable electrolyte additive with steric hindrance effect to balance zinc ion transport and reduction kinetics is one of the effective ways to achieve high-performance aqueous zinc ion batteries. At present, there are no reports on the use of hexacyclic rings with steric hindrance effect as electrolyte additives to suppress zinc negative electrode-related problems and improve device cycle stability. In view of this, the present invention is specially proposed. Summary of the invention
[0004] The purpose of the present invention is to overcome the above defects or deficiencies in the prior art, and to provide a novel aqueous zinc ion battery electrolyte with excellent steric hindrance effect and its application, so as to fundamentally solve the contradiction between fast electrochemical kinetics and slow mass transfer, and further solve the problem of zinc dendrite growth. The purpose of the present invention is achieved by the following technical solutions:
[0005] A novel aqueous zinc ion battery electrolyte with steric hindrance effect, characterized in that it comprises a battery electrolyte additive and a soluble zinc salt, wherein the battery electrolyte additive has a steric hindrance effect, can effectively inhibit zinc dendrites, inhibit side reactions caused by water, and reduce the activity of free water in the electrolyte.
[0006] Furthermore, the battery electrolyte additive is one or more combinations of 4-aminomethylcyclohexanecarboxylic acid, 4-(aminomethyl)cyclohexanecarboxylic acid methyl ester hydrochloride, 4-(aminomethyl)cyclohexylamine, etc.
[0007] Furthermore, the battery electrolyte additive is one or more combinations of 4-aminomethylcyclohexanecarboxylic acid, 4-(aminomethyl)cyclohexanecarboxylic acid methyl ester hydrochloride, 4-(aminomethyl)cyclohexylamine, etc.
[0008] Furthermore, the soluble zinc salt is one or more combinations of zinc sulfate, zinc chloride, zinc bromide, zinc nitrate, zinc acetate, and zinc trifluoromethanesulfonate.
[0009] Furthermore, the concentration of the soluble zinc salt is 1 to 3 mol / L; and the concentration of the battery electrolyte additive is 0.01 to 0.05 mol / L.
[0010] Furthermore, the soluble zinc salt is zinc sulfate with a concentration of 2 mol / L; and the battery electrolyte additive is 4-aminomethylcyclohexanecarboxylic acid with a concentration of 0.02 mol / L.
[0011] Secondly, the present invention also includes the use of a novel aqueous zinc ion battery electrolyte with steric hindrance effect in the preparation of an aqueous zinc ion battery.
[0012] Furthermore, the electrolyte is a novel aqueous zinc ion battery electrolyte with steric hindrance effect, the negative electrode is a zinc metal material, the positive electrode is an intercalation compound, and the positive electrode and the negative electrode are separated by a diaphragm.
[0013] Furthermore, the zinc metal material is one of zinc plate, zinc sheet, zinc foil or three-dimensional zinc foam; the intercalation compound is one of manganese-based materials, vanadium-based materials, and Prussian blue analogs; and the diaphragm is one of glass fiber, qualitative filter paper or polypropylene fiber diaphragm.
[0014] Furthermore, the manganese-based material is MnO2, the vanadium-based material is V2O5, and the Prussian blue analogue is Fe4[Fe(CN)6]3.
[0015] The beneficial effects of the above technical solution are:
[0016] (1) By introducing a lipophilic six-membered ring into a simple organic polar small molecule, the strong interaction characteristics between the functional groups in the small molecule and the zinc ion are retained, the solvation structure of the zinc ion is reconstructed, and the desolvation process of the zinc ion is promoted. At the same time, the solvation sheath of the zinc ion can be expanded, slowing down the rapid electrochemical reduction reaction. A balanced chemical environment is achieved through the dynamic push-pull interaction of the sterically hindered macromolecule on the zinc ion.
[0017] (2) Since the electrolyte additive of the present application has a six-membered ring inside and is rich in oxygen-containing groups, the provided electrolyte is conducive to constructing a water-deficient Zn anode / electrolyte interface on the surface of the zinc negative electrode, promoting smooth and uniform Zn deposition, and delaying the generation of unstable by-products; and it can change the Zn 2+ The solvation chemistry can inhibit the side reactions caused by water and reduce the activity of free water in the electrolyte.
[0018] (3) The present invention is assembled into a Zn||Zn symmetrical battery, and the cycle stability test shows that at 20 mA·cm -2 The battery can be stably cycled for ≥167 days at a current density of 1.5 % and can last for 550 h at a high depth of discharge (DOD) of 80%. It is assembled into a Zn||V2O5 full battery using an ultra-thin zinc sheet (10 μm) at 2Ag -1 , under the conditions of low N / P (4.3) and low E / C (50 μL), the capacity retention rate is still 99.15% after 600 cycles. Therefore, the use of the aqueous zinc ion battery electrolyte provided by the present invention can significantly improve the cycle performance and capacity retention rate of the aqueous zinc ion battery, and provides a promising method for preparing high-performance aqueous zinc metal batteries and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The scanning electron microscope characterization diagram of zinc electrodeposition, in which: a is the Zn anode of Example 1 at 0.5 mA cm -2 a is the SEM characterization of the deposition after the lower cycle, b is the SEM characterization of Comparative Example 1;
[0020] Figure 2 is a schematic diagram of an in-situ optical microscope using the zinc anode of Example 1 and Comparative Example 1 in different electrolytes;
[0021] Figure 3 3D laser scanning confocal microscopy image after cycling using the zinc anode in Example 2;
[0022] Figure 4 It is the long cycle polarization curve of the aqueous zinc ion battery Zn||Zn symmetric battery of the test electrolyte of Example 3 and the reference electrolyte of Comparative Example 2;
[0023] Figure 5 It is a long cycle performance diagram of the Zn||V2O5 battery of the aqueous zinc ion battery prepared by the test electrolyte of Example 4 and the reference electrolyte of Comparative Example 3. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many other ways different from those described herein, so the present invention is not limited to the specific implementation disclosed below.
[0025] Example 1
[0026] The electrodeposition of zinc was carried out by using a composite electrolyte prepared by 4-aminomethylcyclohexanecarboxylic acid (AMCA) and 2 mol / L zinc sulfate solution to verify the effect of 4-aminomethylcyclohexanecarboxylic acid (AMCA) on inducing uniform deposition of zinc ions.
[0027] The operation is as follows: at room temperature, 14.378 g of zinc sulfate heptahydrate and 0.04 g of 4-aminomethylcyclohexanecarboxylic acid (AMCA) are added to 25 ml of deionized water, and ultrasonicated for 20 minutes to completely disperse them to prepare 25 ml of an electrolyte containing 2 mol / L zinc sulfate and 0.02 mol / L 4-aminomethylcyclohexanecarboxylic acid (AMCA).
[0028] The assembled symmetric cell was tested at 0.5 mA cm -2 The deposition morphology after cycling at a current density of Figure 1 As shown in (b), AMCA and Zn 2+ The strong pull-pull interaction between them helps to construct a water-poor Zn anode / electrolyte interface, promotes the preferential Zn deposition on a flat and uniform (002) surface, and suppresses the generation of undesirable byproducts;
[0029] Figure 2 (b) is an in-situ optical microscope photo of zinc deposition. It can be seen that no dendrites and bubbles are generated within 60 minutes of cycling.
[0030] Comparative Example 1
[0031] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, thereby preparing 25 ml of an electrolyte solution containing 2 mol / L zinc sulfate.
[0032] The assembled symmetric cell was tested at 0.5 mA cm -2 The deposition morphology after cycling at a current density of Figure 1 As shown in (a), the Zn deposition structure is loose with many disordered clusters and corrosion pits, which may aggravate the corrosion reaction and the accumulation of byproducts, eventually leading to battery failure.
[0033] Figure 2(a) is an in-situ optical microscopy photograph of zinc deposition. It can be seen that zinc dendrites nucleate within the initial 10 minutes and quickly transform into larger dendrites after 60 minutes, and obvious bubble generation is observed.
[0034] Example 2
[0035] 4-Aminomethylcyclohexanecarboxylic acid (AMCA) is used as an electrolyte additive for aqueous zinc ion batteries; 3D laser scanning confocal microscopy images of the zinc anodes prepared in Example 2 and Comparative Example 2 after cycling.
[0036] Figure 3 (a) is a 3D laser scanning confocal microscopy image of the zinc anode after cycling. The protrusions and rough zinc dendrites and severe corrosion areas appeared on the Zn surface after 50 cycles, with a large height deviation of 77.27μm. In sharp contrast, Figure 3 (b) The electrolyte of AMCA / ZS presents a dense and smooth surface with a fine height variation of 4.23 μm, verifying the steric effect of AMCA in its ability to inhibit and protect dendrites and side reactions.
[0037] Example 3
[0038] 4-Aminomethylcyclohexanecarboxylic acid (AMCA) was used as an electrolyte additive for aqueous zinc-ion batteries to prepare Zn||Zn symmetric batteries and verify the effect of the additive on improving the service life of zinc electrodes.
[0039] The operation is as follows: at room temperature, 14.378 g of zinc sulfate heptahydrate is added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate and 0.02 mol / L 4-aminomethylcyclohexanecarboxylic acid (AMCA) is prepared; zinc foil is used as the positive and negative electrodes, and glass fiber is used as a separator. 120 μL of the above-obtained electrolyte is taken to assemble a CR2032 type button-type symmetrical battery, and a cyclic charge and discharge test is carried out on a Xinwei battery test system, and the working current density is 20 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0040] Comparative Example 2
[0041] At room temperature, 11.5 g of zinc sulfate heptahydrate was added to 5 ml of deionized water and ultrasonicated for 20 min to completely disperse it, thereby preparing 25 ml of an electrolyte solution containing 2 mol / L zinc sulfate.
[0042] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was assembled into a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The current density was 20 mA cm -2, with a surface capacity of 1 mAh cm -2 .
[0043] Test results such as Figure 4 As shown in the figure, the working time of Example 3 using 4-aminomethylcyclohexanecarboxylic acid (AMCA) electrolyte additive is 5100h, while the polarization of Comparative Example 2 increases sharply after 250h of circulation. The greatly increased working time of Example 3 is due to the fact that 4-aminomethylcyclohexanecarboxylic acid (AMCA) forms an adsorption layer on the surface of the zinc negative electrode, which improves the zinc deposition / stripping reaction kinetics and inhibits the growth of zinc dendrites.
[0044] Example 4
[0045] Aqueous zinc ion batteries were prepared using 4-aminomethylcyclohexanecarboxylic acid (AMCA) as an electrolyte additive for aqueous zinc ion batteries. The effect of 4-aminomethylcyclohexanecarboxylic acid (AMCA) electrolyte additive on the capacity retention rate and service life of aqueous zinc ion full batteries was tested.
[0046] The operation is as follows: at room temperature, 14.378g zinc sulfate heptahydrate and 0.04g 4-aminomethylcyclohexanecarboxylic acid (AMCA) are added to 25ml deionized water, and ultrasonicated for 20min to make them completely dispersed, and 25ml electrolyte containing 2mol / L zinc sulfate and 0.02mol / L 4-aminomethylcyclohexanecarboxylic acid (AMCA) is prepared; V2O5 positive electrode preparation process: vanadium oxide (V2O5, Macklin, 99%, 0.3g) is dissolved in 10mL 2M sodium chloride (NaCl) aqueous solution, and after continuous stirring for 72h, the orange-red gel formed is washed several times with deionized water and ethanol in sequence. Then it is dried in a vacuum oven at 80℃ for 12 hours, taken out after cooling, and the solution is filtered, dried, ground and used for later use. Take 80 mg of the V2O5 prepared above, mix it with Super P and polyvinylidene fluoride in a mass ratio of 7:2:1, grind it in an agate mortar for 30 minutes, add N-methylpyrrolidone, stir for 12 hours, and then evenly apply it on the surface of titanium foil with a scraper. After it is completely dried, slice it for later use;
[0047] The V2O5 cathode material prepared above was used as the cathode, zinc foil as the anode, and glass fiber as the separator. 120 μL of the electrolyte was taken to assemble a CR2032 aqueous zinc ion button-type full battery. The cyclic charge and discharge test was carried out in the Xinwei battery test system with a current density of 2A g -1 .
[0048] Comparative Example 3
[0049] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of electrolyte containing 2 mol / L zinc sulfate was prepared. 120 μL of the electrolyte was taken, and the V2O5 positive electrode material prepared in the same way as in Example 4 was used. Zinc foil was used as the negative electrode, and glass fiber was used as the separator to assemble a CR2032 type aqueous zinc ion button-type full battery for cyclic charge and discharge testing in the Xinwei battery test system. The current density was 2A g -1 .
[0050] Test results such as Figure 5 As shown, Example 4 uses ultrathin zinc sheets (10 μm) at 2A g -1 , the discharge capacity under the conditions of low N / P (4.3) and low E / C (50μL) can maintain 99.15% after 1000 cycles, while the discharge capacity of comparative example 3 decays to death after about 420 cycles. This shows that during the cycle process, the addition of 4-aminomethylcyclohexanecarboxylic acid (AMCA) can reduce the formation of zinc dendrites, reduce capacity loss, and improve the reversibility of zinc deposition / stripping reaction.
[0051] Compared with the existing technology, the present invention is assembled into a Zn||Zn symmetrical battery. The cycle stability test shows that the battery has a stable performance at 20 mA·cm -2 The battery can be stably cycled for ≥167 days at a current density of 1.50 g / cm2 and can last for 550 h at a high depth of discharge (DOD) of 80%. The battery is assembled into a Zn||V2O5 full battery using an ultra-thin zinc sheet (10 μm) at 2A g / cm2. -1 , under the conditions of low N / P (4.3) and low E / C (50 μL), the capacity retention rate is still 99.15% after 600 cycles. Therefore, the use of the aqueous zinc ion battery electrolyte provided by the present invention can significantly improve the cycle performance and capacity retention rate of the aqueous zinc ion battery, and provides a promising method for preparing high-performance aqueous zinc metal batteries and other fields.
[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A novel aqueous zinc ion battery electrolyte with steric hindrance effect, characterized in that: The invention comprises a battery electrolyte additive and a soluble zinc salt. The battery electrolyte additive has a steric hindrance effect, can effectively inhibit zinc dendrites, inhibit side reactions caused by water, and reduce the activity of free water in the electrolyte.
2. A novel aqueous zinc ion battery electrolyte with steric hindrance effect according to claim 1, characterized in that: The battery electrolyte additive is one or more combinations of 4-aminomethylcyclohexanecarboxylic acid, 4-(aminomethyl)cyclohexanecarboxylic acid methyl ester hydrochloride, 4-(aminomethyl)cyclohexylamine, and the like.
3. A novel aqueous zinc ion battery electrolyte with steric hindrance effect according to claim 1, characterized in that: The soluble zinc salt is one or more combinations of zinc sulfate, zinc chloride, zinc bromide, zinc nitrate, zinc acetate, and zinc trifluoromethanesulfonate.
4. A novel aqueous zinc ion battery electrolyte with steric hindrance effect according to claim 1, characterized in that: The concentration of the soluble zinc salt is 1-3 mol / L; the concentration of the battery electrolyte additive is 0.01-0.05 mol / L.
5. A novel aqueous zinc ion battery electrolyte with steric hindrance effect according to claim 4, characterized in that: The soluble zinc salt is zinc sulfate with a concentration of 2 mol / L; and the battery electrolyte additive is 4-aminomethylcyclohexanecarboxylic acid with a concentration of 0.02 mol / L.
6. Use of the novel aqueous zinc ion battery electrolyte with steric hindrance effect according to claim 1 in the preparation of aqueous zinc ion batteries.
7. An aqueous zinc ion battery according to claim 6, characterized in that: The electrolyte is a new type of aqueous zinc ion battery electrolyte with steric hindrance effect. The negative electrode is a zinc metal material, the positive electrode is an intercalation compound, and the positive electrode and the negative electrode are separated by a diaphragm.
8. An aqueous zinc ion battery according to claim 7, characterized in that: The zinc metal material is one of zinc plate, zinc sheet, zinc foil or three-dimensional zinc foam; the intercalation compound is one of manganese-based materials, vanadium-based materials, and Prussian blue analogs; and the diaphragm is one of glass fiber, qualitative filter paper or polypropylene fiber diaphragm.
9. An aqueous zinc ion battery according to claim 8, characterized in that: The manganese material is MnO2, the vanadium material is V2O5, and the Prussian blue analog is Fe4[Fe(CN)6]3.
Citation Information
Cited By
Aqueous zinc ion battery electrolyte containing NAL additive as well as preparation method and application of aqueous zinc ion battery electrolyte
CN122267323A